The Role of Coffee and Its Bioactive Components in Platelet Function and Aging - Silva-Weiss, A (Bentham Science Publishers, 2021)
Cardiovascular diseases (CVD) are known to be the world s leading cause of death and different factors are known to increase the risk of death, including aging, mainly due to increased oxidative stress and inflammation observed in older people. Acute myocardial infarctions and cerebrovascular accidents belong to CVD, and are the ones that cause the most deaths and disabilities, where greater platelet activation plays an important role in pathophysiology. These diseases are more prevalent in older people, which have a clear relationship with increased platelet function and are strongly related to aging. Platelet function is affected by diet, which varies in its requirements and characteristics according to age. Coffee belongs to the family of diet elements that can alter platelet function and an increase in coffee consumption with advancing age, and a U-shaped correlation with the risk of CVD have been reported. However, the effect of coffee consumption and its bioactive compounds on platelet function and aging presents controversial evidence, and therefore, a complex effect is not fully elucidated in the cardiovascular system. This review focuses on the relationship between coffee consumption (and its constituent bioactive compounds), and platelet function, and aging. © 2021 Bentham Science Publishers.